Rapid Plastic Deformation of Cancer Cells Correlates with High Metastatic Potential (Adv. Healthcare Mater. 8/2022). Issue 8 (20th April 2022) - Yan, Zishen; Xia, Xingyu; Cho, William C.; Au, Dennis W.; Shao, Xueying; Fang, Chao; Tian, Ye; Lin, Yuan
Abstract : Cell Plasticity During metastasis, cancer cells must severely deform themselves to squeeze through tight spaces in the surrounding tissue or junctions between capillary endothelial cells. Therefore, the capability of tumor cells to undergo plastic deformations could greatly facilitate their metastasis. Using a novel microfluidic setup, the study in article number 2101657 by William C. Cho, Yuan Lin, and co‐workers, shows that the invasiveness of cancer cells is indeed correlated with their plastic response.